Quercetin inhibits colorectal cancer cells induced-angiogenesis in both colorectal cancer cell and endothelial cell through downregulation of vegf-a/vegfr2 - Tamonwan Uttarawichien (2022)
Colorectal cancer (CRC) aggressiveness is caused by cancer angiogenesis which promotes the cancer growth and metastasis associated with poor prognosis and poor survival. The vascular endothelial growth factor-A (VEGF-A) and its receptor (VEGFR-2) form the major signaling pathway in cancer angiogenesis. This study aimed to investigate the anti-angiogenesis activity of quercetin in both colorectal cancer cells and endothelial cells. The tube formation of human vein endothelial cells (HUVECs) was determined by using conditioned media of HT-29 cells treated with quercetin co-cultured with HUVECs. The VEGF-A and NF-κB p65 protein expressions in the quercetin-treated HT-29 cells were determined by fluorescence assay and Western blot analysis. The VEGFR-2 protein expression in HUVECs was determined after they were co-cultured with the quercetin-treated HT-29 cells. Quercetin markedly decreased the HT-29 cell-induced angiogenesis in HUVECs. NF-κB p65 and VEGF-A protein expression were also inhibited by quercetin. Moreover, quercetin significantly inhibited VEGFR-2 expression and translocation in HUVECs after they were co-cultured with high dose quercetin-treated HT-29 cells. Taken together, quercetin had an anti-angiogenesis effect on VEGF-A inhibition related to the NF-κB signaling pathway in the HT-29 cells and reduced VEGFR-2 expression and translocation in HUVECs.